Pengembangan Media Pembelajaran Etnobook Digital: Pop Up Flipbook Sebagai Sarana Enkulturasi Literasi pada Siswa Sekolah Dasar - Tria Adista; Widiya; Ananda Dwi Safitri; Astrid Juliyanti; Maulina Hendrik; Eryza Tiara Dzulqa (CENDEKIAWAN, 2025)
This research is motivated by the challenge of integrating local cultural values into education, especially in elementary schools, amidst the growing wave of globalization. Cultural preservation and increasing student literacy are two aspects that need to be considered in the teaching and learning process. Therefore, this study aims to develop a digital learning media in the form of a digital pop-up flipbook with cultural content that is valid and practical as an effort to literacy for elementary school students. The research method used is research and development with the ADDIE model, which includes needs analysis, design, development, implementation, and evaluation. Data collection techniques use interview techniques, assessment questionnaires, and observation. Data analysis techniques use descriptive and quantitative analysis techniques. The results obtained from this study are learning media developed in the form of a pop-up flipbook containing the culture of Bangka Belitung which has been tested for media and material validity as well as media practicality. The results of the validity test through three media experts were 88% and the results of the material validity test were 94%. In addition, practicality tests have been carried out through teacher and student response assessments of 81%. Thus, developing digital learning media with cultural content functions as a learning aid and a means to strengthen cultural identity and student literacy.